Strategi Content Marketing pada Media Sosial Instagram Sebagai Strategi Pemasaran Digital Centro Barbershop - Ibnu Hiban Farras; Sihabudin; Robby Fauji (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted because of increasing competition in marketing, especially related to the use of marketing content on Instagram. The purpose of this research is to understand the content marketing strategy used by Centro Barbershop to increase sales and face business competition. The research method used is qualitative, with primary data collection through interviews and direct observation with the Centro Barbershop owner, Centro Barbershop marketer management and Centro Barbershop consumers as well as collecting secondary data from journal articles and library studies. The data collected was analyzed using content analysis. The research results show that Centro Barbershop implements a content marketing strategy through four channels of attention (attention), interest (interest), desire (desire) and action. As a recommendation, it is recommended that centro barbershop adopt a marketing content strategy that involves attractive visuals, unique stories, customer reviews, and clear actions to stimulate audience interest and desire and encourage them to try barbering services and make further purchases or interactions.